2013
DOI: 10.1021/nl304735k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Electronic Transport Properties of DNA Translocation through Graphene Nanopores

Abstract: Graphene layers have been targeted in the last years as excellent host materials for sensing a remarkable variety of gases and molecules. Such sensing abilities can also benefit other important scientific fields such as medicine and biology. This has automatically led scientists to probe graphene as a potential platform for sequencing DNA strands. In this work, we use robust numerical tools to model the dynamic and electronic properties of molecular sensor devices composed of a graphene nanopore through which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 48 publications
3
113
1
Order By: Relevance
“…Similar results were obtained from various theoretical calculations, where electronic transport was studied using DFT and NEGF for different types of ribbons (width ∼3 nm and pore diameter ∼1.5nm) in the absence and presence of each of the four DNA nucleobases [72][73][74][75][76][77][78][79].…”
Section: Inplane Transport Of a Graphene Nanoribbon With A Nanoporesupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were obtained from various theoretical calculations, where electronic transport was studied using DFT and NEGF for different types of ribbons (width ∼3 nm and pore diameter ∼1.5nm) in the absence and presence of each of the four DNA nucleobases [72][73][74][75][76][77][78][79].…”
Section: Inplane Transport Of a Graphene Nanoribbon With A Nanoporesupporting
confidence: 84%
“…Base-distinct current variations were found, in the order of ∼1 µA at 100mV bias, much larger than what can be expected for armchair edged ribbons where these edge currents are absent. These results were, however, contradicted by a self-consistent DFT study on zigzag GNRs [75] that showed that the respective bases can only be distinguished when transport is conducted away from the Fermi level. In another interesting study, ribbons with a finite length along the ribbon were compared to quantum point contact structures, which essentially are ribbons in the limit of zero length [76].…”
Section: Inplane Transport Of a Graphene Nanoribbon With A Nanoporementioning
confidence: 82%
See 1 more Smart Citation
“…It is generally believed that the premise of this method is how to obtain proper nanopores and how to design effective fluidic device. Till now, natural nanopores in biomembranes [15,16] and artificial nanopores in inorganic films [17][18][19] are two major types of pores used in this area, while nanopores in polymer membranes obtained by track-etching method also can provide other possible choices [20][21][22][23]. Since the transport of mass and charge in the confined nanochannels, novel phenomena which cannot be observed in the bulk solutions will occur [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] By fabricating nanogaps or nanopores on the graphene sheet and then propelling single molecules to electrophoretically translocate through the gap/pore, information regarding the target molecules can be recorded and used for characterizing the molecules. This information can be either the longitudinal ionic current blockage due to the transient dwelling of molecule in the gap/pore, [2][3][4]9 or the transverse tunneling current through the molecule measured by the electrodes embedded in the pore.…”
Section: Introductionmentioning
confidence: 99%